Bentonite-humic acid improves soil organic carbon, microbial biomass, enzyme activities and grain quality in a sandy soil cropped to maize (Zea mays L.) in a semi-arid region - Lei ZHOU; Sheng-tao XU; Carlos M. MONREAL; Neil B. MCLAUGHLIN; Bao-ping ZHAO; Jing-hui LIU; Guo-cheng HAO (Journal of Integrative Agriculture, 2022)
A bentonite-humic acid (B-HA) mixture added to degraded soils may improve soil physical and hydraulic properties, due to effects such as improved soil structure and increased water and nutrient retention, but its effect on soil physicochemical and biological properties, and grain quality is largely unknown. The effect of B-HA, added at 30 Mg ha−1, was studied at 1, 3, 5 and 7 years after its addition to a degraded sandy soil in a semi-arid region of China. The addition of B-HA significantly increased water-filled pore space and soil organic carbon, especially at 3 to 5 years after its soil addition to the soil. Amending the sandy soil with B-HA also increased the content of microbial biomass (MB)-carbon, -nitrogen and -phosphorus, and the activities of urease, invertase, catalase and alkaline phosphatase. The significant effect of maize (Zea mays L.) growth stage on soil MB and enzyme activities accounted for 58 and 84% of their total variation, respectively. In comparison, B-HA accounted for 8% of the total variability for each of the same two variables. B-HA significantly enhanced soil properties and the uptake of N and P by maize in semi-arid areas. The use of B-HA product would be an effective management strategy to reclaim degraded sandy soils and foster sustainable agriculture production in northeast China and regions of the world with similar soils and climate.